2018
DOI: 10.14710/nmjn.v7i2.15177
|View full text |Cite
|
Sign up to set email alerts
|

Negative Air Pressure on Wet Cupping in Decreasing Blood Pressures in Hypertensive Patients

Abstract: Background: Wet cupping, furthermore mentioned cupping, decreases blood pressures through the level of negative air pressures added by hydrostatics filtration pressure to reinforce the power of fluids filtration in capillaries. However, an appropriate negative air pressure to decrease blood pressure remains an uncertainty. Purpose:This study aimed to analyze negative air pressure differences on cupping in decreasing blood pressures in hypertensive patients. Methods: This is a quasi-experimental design conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
2
2
0
1
Order By: Relevance
“…Meanwhile, there was a difference in pulse frequency from week 2 to 6. These results are consistent with previous research that found a significant difference in systolic blood pressure values between the intervention and control groups after 2 weeks of follow-up [12]. Another Chinese research stated wet cupping lowers blood pressure at the 4 th week after therapy [13].…”
Section: Discussionsupporting
confidence: 92%
“…Meanwhile, there was a difference in pulse frequency from week 2 to 6. These results are consistent with previous research that found a significant difference in systolic blood pressure values between the intervention and control groups after 2 weeks of follow-up [12]. Another Chinese research stated wet cupping lowers blood pressure at the 4 th week after therapy [13].…”
Section: Discussionsupporting
confidence: 92%
“…It is undeniable that people in Indonesia not only believe in conventional medicine (Ritonga et al, 2017) but also in shaman for the medication (Sherliawati, 2014). It is in line with a study in rural Yogyakarta, Indonesia, which also found that the patients with hypertension tend to have the preference to manage hypertension on their own, especially to use traditional or alternative medicines and herbs, such as cucumber, avocado leaves (Rahmawati & Bajorek, 2018), aloe vera (Yuliawati et al, 2021, celery leaves (Isnainy et al, 2021), cupping therapy (Darmawan et al, 2017), acupuncture (Hidayah et al, 2021), and others to replace the prescribed medication. Therefore, during the assessment of patients with hypertension, nurses need to ask whether the patients use traditional medicine or combine it with the prescribed drugs before visiting public health centers to improve shared understanding and decision-making.…”
Section: Discussionsupporting
confidence: 81%
“…In the study (Mukhlis et al, 2020) Cupping was performed at the top of the head and neck with an average decrease in blood pressure of 19.6 mmHg in SBP and 11.2 mmHg in DBP. In a study conducted by (Darmawan et al, 2017) cupping in hypertension patients with a total of 36 samples was carried out at the midline point between the two shoulders (Alkahil) there was a decrease in SBP blood pressure of 3.28 mmHg and 2.89 mmHg in DBP, Likewise research conducted by (Rahman et al, 2020) cupping was carried out at the midline point between the two shoulders in 100 samples with 50 women and 50 men, there was a decrease in blood pressure of 12 mmHg in women and 9 mmHg in men. man.…”
Section: Discussionmentioning
confidence: 99%